A retrospective study of burden, pattern, and site of pediatric tuberculosis patients registered in the district tuberculosis center of Jabalpur district - Arvind Sharma; Sunita Patel; Prince Kumar Lodhi; Aprajita (Asian Journal of Medical Sciences)
Background: Tuberculosis (TB) is a major global public health threat and its impact on pediatric population is particularly concerning. India has the highest fraction of the world’s TB burden. TB is a disease with high morbidity and mortality. Aiming for eradication in 2025 announced by the honorable Prime Minister which is ahead for global eradication which is 2030.